1987
DOI: 10.1152/ajprenal.1987.252.1.f83
|View full text |Cite
|
Sign up to set email alerts
|

Modification of tubuloglomerular feedback signal by dietary protein

Abstract: Compared with the effects of a 6% protein diet, feeding rats a 40% protein diet for 10 days increases glomerular filtration rate and decreases the activity of the tubuloglomerular (TG) feedback control system. The decrease in TG feedback activity results from an increase in the threshold at which the loop of Henle flow rate initiates feedback responses. To determine whether this protein-dependent shift in the TG feedback response curve is caused by changes in either the signal or the sensing mechanism in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0
2

Year Published

1988
1988
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 0 publications
3
42
0
2
Order By: Relevance
“…Prostaglandins are known to mediate renin release and may therefore be involved in the dietary protein induced changes in renin (24). High protein diets also result in increased loop of Henle sodium reabsorption and hence decreased sodium delivery to the macula densa, an effect that would also be expected to stimulate renin release (25).…”
Section: Discussionmentioning
confidence: 99%
“…Prostaglandins are known to mediate renin release and may therefore be involved in the dietary protein induced changes in renin (24). High protein diets also result in increased loop of Henle sodium reabsorption and hence decreased sodium delivery to the macula densa, an effect that would also be expected to stimulate renin release (25).…”
Section: Discussionmentioning
confidence: 99%
“…Microperfusion studies by Seney et al (68) determined that protein-induced increases in GFR result from changes in the tubuloglomerular feedback (TGF) system. Their studies found that the sensing mechanism of the TGF system was rendered less responsive by high protein intake and that the diminished TGF was caused, at least in part, by a reduced early distal NaCl concentration, without a change in early distal tubule osmolality (69).…”
Section: Urea Recycling and Regulation Of Gfr By High-protein Dietsmentioning
confidence: 99%
“…Studies by Seney and Wright determined that this increase in GFR results from changes in the tubuloglomerular feedback (TGF) system (17,18). Furthermore, they determined that it is not an actual change in the sensing mechanism of the TGF response that is affected by high-protein diet, but rather it is an effect on the signal causing the TGF response.…”
Section: Effect Of High Protein Intake On Gfr: Possible Role Of Ureamentioning
confidence: 99%